Research on the characteristics of the refrigeration, heating and hot water combined air-conditioning system. (October 2021) - Pei, Xiangxiang; Guo, Yabin; Guo, Yuancheng; Li, Ruixin; Yang, Jianzhong; Mao, Mingrui
Highlights: A new air conditioning system is explored by experiment. The system starts mode H is the most stable, and the maximum superheat is 11°C. A unique phenomenon occurs in the production of hot water. The system fluctuates periodically in the refrigeration mode. The drop in discharge pressure can be used as a parameter for defrost control. Abstract: Air source heat pump (ASHP) and heat pump water heater (HPWH) have the advantages of convenience and high efficiency. The newly proposed refrigeration, heating and hot water combined air-conditioning system (RHHAC) combines traditional ASHP with HPWH. The demands of users for cooling, heating and hot water are effectively satisfied with this equipment. In this study, five groups of experiments were conducted to study the starting and operating characteristics of the system. Besides, two sets of experimental cases were carried out to explore the operating characteristics of the system under the frosting process. Results show that the maximum superheat degree is 11°C when the system starts in hot water mode, while the maximum superheat degree is more than 22°C when the system starts in the other modes. As the temperature of hot water rises when the system runs in hot water mode, the maximum value of the discharge pressure can reach 3.7MPa. Besides, the analysis parameters will have regular pulsations when the system is in cooling mode. For example, in the experimental case 5, the fluctuation range of the superheat degree is 5.1°C-16.2°C.